Gambaran Angka Peroksida Pada Minyak Jelantah di Warung Penyetan Wilayah Mancasan Yogyakarta - Dian Wuri Astuti; Siti Fatimah; Embang Albari (Biogenesis: Jurnal Ilmiah Biologi, 2015)
The frying pan thermal-kimia was a process that produces characteristic of food with the brown colour of golden. One of the parameters of the decline in quality cooking oil is the number of peroxide. During the frying pan, cooking oil will suffer at high temperatures warning 160-1800C in long time. The main damage is the emergence of a rancid scent while damage other covering elevated levels of free fatty acid, the peroxide, thickness the emergence of oil, the establishment of foam and the dirt on seasoning of material that fried. Based on cooking oil used in a penyetan stall is generally of cooking oil used repeatedly. The use of oil can improve the former repeatedly peroxide in the cooking oil. Research objectives is to know the image of the peroxide on a former oil in a penyetan stall areas Mancasan Yogyakarta. This research is descriptive research. Laboratory test to research is iodometry method. A penyetan stall to research this a total of eight-penyetan stall located in the Mancasan Yogyakarta. Research conducted on eight a penyetan stall areas Mancasan in Yogyakarta obtained the number of the peroxide of 1,10 meq/kg until 5,74 meq/kg. From the result of research conducted on a penyetan stall there are 62.5% penyetan stall peroksida number exceeding the limit of standards and 37,5% still within the limits of cooking oil according to quality standard SNI 7709:2012.Keywords: cooking oil former, number of peroxide